Raman and FTIR Study of a 2, 3'-difluoro-4''-isothiocyanato-4-propyl-1, 1':4', 1''-terphenyl compound or C3P(3F)P(3F)P-NCS. (4th March 2019) - Lyndem, Marpliephar; Bhattacharjee, Ayon; Dabrowski, Roman
Abstract: A vibrational spectroscopy study of a laterally fluorinated terphenyl liquid crystalline (LC) compound is presented in this paper. The study consists of temperature dependent Raman study and room temperature FTIR spectroscopy. The molecular structure was optimized using Density Functional Theory (DFT) with B3LYP functional and 6-31G (d, p) basis set and some structural properties have been noted. From the detailed study of the temperature dependent Raman spectra, the nature of the phase transition of the LC compound was investigated. It was found that the quadrant stretching modes and the CH bending modes of the phenyl rings display significant changes at Cr-N transition and N-I transition. This study therefore throws some light on the nature of transitions. From the FTIR study, it was found that the CC vibrations of the rings and NCS vibrations have large absorptions while the CH bending modes have less absorption.